The Representation of Ideology in Nadiem Makarim Case by Tech in Asia: An Appraisal and Critical Discourse Analysis Approach - Dini Eka Maulida; Madeleine Winday; T. Thyrhaya Zein; Nurlela (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2026)
This study investigates the representation of Nadiem Makarim in TikTok content published by Tech in Asia by employing Appraisal Theory and Critical Discourse Analysis (CDA). The research aims to identify the evaluative language used in the discourse and examine the ideological tendencies reflected in the media representation. The data consist of 109 clauses collected from opinion, interview, straight news, and hard news content related to the media-reported alleged corruption case involving Nadiem Makarim. A qualitative descriptive approach is employed in this study. The results show that engagement is the most dominant appraisal resource (71.5%), followed by attitude (20.2%) and graduation (8.3%). The frequent use of heteroglossic and monoglossic resources suggests that Tech in Asia constructs legitimacy through selected external voices, particularly from the technology and business sectors. The findings also indicate that Nadiem Makarim is predominantly represented as an innovator and entrepreneurial leader rather than being primarily associated with the legal allegations. From the perspective of Fairclough’s social practice framework, the discourse appears to reflect values related to innovation, entrepreneurial leadership, legal certainty, and technological development. Overall, this study demonstrates how evaluative language contributes to the construction of meaning and representation within contemporary digital media discourse.